Acute Promyelocytic Leukemia A Clinical Guide (Springer International Publishing, 2018)
This book provides a comprehensive overview on the clinical issues and biology of acute promyelocytic leukemia (APL) and on the molecular mechanisms of targeted therapy with ATRA and ATO. The text covers major topics such as the pathophysiology of APL coagulopathy, biologic and clinical differences between children and adults with APL, and the role of minimal residual disease monitoring. Additionally, the book summarizes historical, current, and future treatment strategies in both adults and children, while highlighting the most recent therapeutic recommendations for relapsed disease and the evolving indications for autologous and allogeneic stem cell transplant. This volume also features chapters focusing on secondary APL and therapy, late effects, rare presentations such as APL in the elderly and during pregnancy, and rare APL variants that may represent therapeutic challenges. Written by top experts in the field, Acute Promyelocytic Leukemia: A Clinical Guide is a valuable resource for clinicians and researchers who treat and investigate this disease in children and adults.